The Sisters Grimm : the unusual suspects - Buckley, Michael; Ferguson, Peter, 1968- (New York : Amulet Books, 2005)
Although filled with anger over her parents' disappearance, eleven-year-old Sabrina Grimm--along with her grandmother, sister, and several fairy-tale characters--tries to discover who has killed her teacher.
Keywords: Anger -- Juvenile fiction; Sisters -- Juvenile fiction; Grandmothers -- Juvenile fiction; Schools -- Juvenile fiction; Characters in literature -- Fiction; Anger -- Fiction; Sisters -- Fiction; Grandmothers -- Fiction; Schools -- Fiction; Mystery and detective stories; Children's stories